Friendly directors and the cost of regulatory compliance - Wintoki, M. Babajide; Xi, Yaoyi (Journal of Corporate Finance, 2019)
We present evidence that, following the passage of the Sarbanes-Oxley Act, firms responded to the increased requirement for outside director monitoring by substituting insiders with outside directors who have social or professional connections to their CEOs. This substitution was most significant in firms that have higher outside director monitoring costs – small, young firms, firms outside the S&P 1500 index, and firms with low analyst scrutiny. The addition of these “friendly” directors did not reduce firm performance, suggesting that it may have been an efficient response by firms aimed at lowering the additional monitoring costs imposed by the new regulations. Our findings suggest that, as with many other aspects of board composition, the determinants and consequences of appointing friendly directors vary with the costs and benefits of outside director monitoring.